Behçet's syndrome in Scotland. Issue 801 (July 1992) - Jankowski, J.; Crombie, I.; Jankowski, R.
Abstract : We present the clinical details and HLA typing of 15 Celtic Caucasian patients (four male, 11 female) with Behçet's syndrome (International Study Group criteria). The males affected were younger than the affected females, and three of these males had severe uveal involvement. Two of the 15 patients had the A2 Bw6 Dr4 haplotype but this did not confer family penetrance. Eight had gastrointestinal involvement: two females required ileostomy, two females had chronic diarrhoea, one female had severe ileitis and oesophageal lesions, two males had peptic ulcers, and one female had a peptic ulcer and primary biliary cirrhosis. All of those who developed gastrointestinal symptoms had either the Dr4 or the Dr7 antigens. This study is the largest HLA survey of Celtic Caucasians with Behçet's syndrome. The clinical features and HLA haplotypes are markedly different from 'Arab' and 'Japanese' varieties of Behçet's syndrome. The expression of the Dr4 and Dr7 antigens in those with gastrointestinal involvement possibly implicates class II antigens (Dr) in the pathogenesis of the manifestations of Behçet's disease in the bowel.